Italijanske jezikovne prvine v spontanem govoru v Slovenski Istri - Volk, Jana (Annales. Series historia et sociologia, 2007)
The article deals with the presence of Italian linguistic elements in spontaneous speech in Slovene Istria. In this area, the Slovene and Italian languages have been in contact for centuries, influencing each other on various linguistic levels. The article analyses spontaneous speech, which is not standardised; this sometimes made it difficult to establish whether certain analysed cases represented a feature of spontaneous speech or interference of the Italian language. The analysis was conducted on a corpus of spontaneous speech created on the basis of an audio recording of a conversation between a car salesman and a customer. The examples of interference were analysed on the levels of lexicology, morphology and syntax,and classified in the following sections: Noun Gender, Noun Number, Noun Case, Use of the Preposition "od", Linking with Prepositions, Comparison of Adjectives, Numerals, Personal Pronoun Replacing an Object Expressed by a Noun, Pronoun "ki", Use of the Infinitive, Use of the Present Tense for Expressing Future Time, Aspect, Reflexivity of the Verb, Word Order, Simple Sentence, Main Clause, Subordinate Clause, Calques, Lexis and Idioms. Most cases of Italian language interference were found on the level of lexis - they represent almost one half of the cases of interference from the material analysed. There emerges the question whether the results would have been different if the speech had been prepared in advance or if the two speakers knew their conversation was being recorded. It has been proven that the presence of recording devices can hinder spontaneity. If speakers have the time to prepare the text, they produce it more carefully and with more regard to the standards of the literary language, which in this case could have been perhaps reflected in a lower frequency of Italian language interference. Nevertheless, the aim of the present article is to point out some characteristics of the spoken language in an informal speech situation in Slovene Istria, where the language develops in conformity with the rules of the Slovene spoken language and at the same time in intense contact with the Italian language.
Keywords: Italian; italijanščina; jeziki v stiku; pogovorni jezik; Slovene; Slovenian Istria; Slovenska Istra; slovenščina